Soft Robots: Electrically Driven Microengineered Bioinspired Soft Robots (Adv. Mater. 10/2018). Issue 10 (6th March 2018) - Shin, Su Ryon; Migliori, Bianca; Miccoli, Beatrice; Li, Yi‐Chen; Mostafalu, Pooria; Seo, Jungmok; Mandla, Serena; Enrico, Alessandro; Antona, Silvia; Sabarish, Ram; Zheng, Ting; Pirrami, Lorenzo; et al.
Abstract : A bioinspired soft robot is designed by mimicking the shape and biomechanical model of a batoid fish, as described by Su Ryon Shin, Ali Khademhosseini, and co‐workers in article number 1704189 . The biomimetic structure is fabricated by self‐actuating cardiac muscles on a hierarchically structured hydrogel scaffold with flexible gold microelectrodes. The robot shows controllable actuating motion aligned with the direction of the contractile force of the cardiomyocytes by localized electrical stimulation via flexible microelectrodes.